Which microbiome are we talking about? Contrasted diversity patterns and eco-evolutionary processes between gill and intestinal microbiomes of Antarctic fairy shrimps - Schwob, Guillaume; Cabrol, Léa; Vidal, Paula M.; Tapia, Yasna C.; Moya, Fernando; Contador, Tamara; Orlando, Julieta; Maturana, Claudia S. (Frontiers in Ecology and Evolution, 2024)
Metazoans comprise multiple physical niches (“microenvironments”), each colonized by unique microbiomes that contribute to their hosts’ evolutionary dynamics, influencing their health, physiology, and adaptation to changing environments. Most wildlife microbiome studies focus on higher metazoans and multiple host microenvironments, while studies of lower species often concentrate on a single microenvironment, sometimes pooling whole bodies or specimens. This is particularly evident in small-sized animals, such as freshwater meiofaunal invertebrates, thus impeding a holistic understanding of microbiome assembly across host microenvironments and its relation with host population genetics. Leveraging the anostracan fairy shrimp Branchinecta, which has easily discernible organs and expected high levels of intraspecific genetic divergence, we aimed to investigate the microbiome assembly processes and test the phylosymbiosis signal in two microenvironments (gill and intestine) across four host populations of Branchinecta gaini within Maritime Antarctica, using 16S rRNA metabarcoding. Our results showed that the gill and intestine harbor strikingly different microbiomes resulting from the B. gaini ecological filtering of the surrounding environment microbial community. Both microenvironments exhibit their respective core microbiomes, yet the gill’s core microbiome is narrower and constitutes a smaller proportion of the overall bacterial community compared to that of the intestine. Within each host population (i.e. each sampling site), the microbiome assembles through distinct eco-evolutionary processes in both microenvironments, mostly stochastically (ecological drift) in the gill and deterministically (variable selection) in the intestine. Across different B. gaini populations, variable selection dominates in driving compositional divergence of both microenvironment microbiomes, although to a lesser extent in the gill. Lastly, our study reveals robust correlation between host intraspecific genetic structure and intestine microbiome composition, providing evidence of phylosymbiosis in anostracans. Contrastingly, phylosymbiosis was less pronounced in the gill microbiome. We discuss the potential differences in ecological filtering between each host microenvironment that may underlie the difference in the strength of phylosymbiosis. Our study highlights the relevance of considering host microenvironment and intraspecific levels in testing the phylosymbiosis hypothesis to better understand the intricate eco-evolutionary relationships between hosts and their microbiomes.